2020
DOI: 10.3390/microorganisms8040605
|View full text |Cite
|
Sign up to set email alerts
|

Natronomonas salsuginis sp. nov., a New Inhabitant of a Marine Solar Saltern

Abstract: A halophilic archaeon, strain F20-122T, was isolated from a marine saltern of Isla Bacuta (Huelva, Spain). Cells were Gram-stain-negative, aerobic, and coccoid in morphology. It grew at 25–50 °C (optimum 37 °C), pH 6.5–9.0 (optimum pH 8.0), and 10–30% (w/v) total salts (optimum 25% salts). The phylogenetic analyses based on the 16S rRNA and rpoB’ genes showed its affiliation with the genus Natronomonas and suggested its placement as a new species within this genus. The in silico DNA–DNA hybridization (DDH) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…The presence of rhodopsin like-sequences in most Halomicroarcula genomes suggest a versatile metabolic flexibility in illuminated conditions for members of this genus. These results are in accordance with recent comparative genomic studies in other haloarchaeal genera ( Durán-Viseras et al, 2019a , 2020 , 2021 ) in which rhodopsins were also identified, and also with previous metagenomic analyses on hypersaline systems ( Fernández et al, 2014 ; Vera-Gargallo and Ventosa, 2018 ) that showed the existence of a large number of rhodopsin coding genes, clearly indicating the wide use of light by haloarchaea in these extreme habitats.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of rhodopsin like-sequences in most Halomicroarcula genomes suggest a versatile metabolic flexibility in illuminated conditions for members of this genus. These results are in accordance with recent comparative genomic studies in other haloarchaeal genera ( Durán-Viseras et al, 2019a , 2020 , 2021 ) in which rhodopsins were also identified, and also with previous metagenomic analyses on hypersaline systems ( Fernández et al, 2014 ; Vera-Gargallo and Ventosa, 2018 ) that showed the existence of a large number of rhodopsin coding genes, clearly indicating the wide use of light by haloarchaea in these extreme habitats.…”
Section: Resultssupporting
confidence: 92%
“…Phenotypic features of strains F24A T , F28, F27 T , and F13 T were performed according to the minimal standards established for the taxonomic description of novel taxa of the class Halobacteria ( Oren et al, 1997 ) and following the methodology previously described by Durán-Viseras et al, 2020 . Halomicroarcula pellucida CECT 7537 T , Halomicroarcula salina JCM 18369 T and Halomicroarcula limicola JCM 18640 T were used as reference strains for taxonomic comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Natronomonas is a halophilic genus, deeply studied for possible biotechnological applications, for which only four species have been described so far [60]. The high abundance of this genus in waters of the saltern of MdS with low salinity (13.1%) differs from the optimal growth conditions currently reported (including salt concentrations around 25%) and leads to the hypothesis of the presence of new species.…”
Section: Taxonomic Profilesmentioning
confidence: 99%
“…The genus Natronomonas (belonging to family Haloarculaceae , order Halobacteriales , class Halobacteria ) was established in 1997 and currently contains three validly published species: Natronomonas pharaonis [4], Natronomonas moolapensis [5] and Natronomonas gomsonensis [6], and a effectively published species, ‘ Natronomonas salsuginis ’ [7]. N.…”
Section: Full-textmentioning
confidence: 99%
“…The genus Natronomonas (belonging to family Haloarculaceae, order Halobacteriales, class Halobacteria) was established in 1997 and currently contains three validly published species: Natronomonas pharaonis [4], Natronomonas moolapensis [5] and Natronomonas gomsonensis [6], and a effectively published species, 'Natronomonas salsuginis' [7]. N. pharaonis is the type species of the genus, an extremely haloalkaliphilic archaeon that was isolated from alkaline salt-saturated brine samples of eutrophic desert lakes in Wadi Natrun, Egypt [8].…”
mentioning
confidence: 99%